2015
DOI: 10.1016/j.jcte.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine treatment generates an abnormal uterine contractility patterns in an in vitro animal model

Abstract: ObjectiveAbnormal uterine contraction patterns were recently demonstrated in uterine strips from pregnant women treated with Levothyroxine (T4). These abnormalities were correlated with an increased risk of C-section delivery and associated surgical complications. To date, no study has investigated whether uterine contractility is modified by hypothyroidism or T4 treatment. Herein, we analyze the physiological role of T4 on uterine contractions.Study designFemale non-pregnant Sprague–Dawley rats (N = 22) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…[21][22][23] Therefore, a prolonged uterine quiescent phase in late pregnancy could be hypothesized as a cause of fetal breech presentation, in addition to an inefficient uterine contraction pattern induced by a high thyroxine concentration state, resulting in an increase of overall CD rate. 4,12,21,[24][25][26] However, our study cannot support this hypothesis as the prescribed dosage, the women's adherence to levothyroxine therapy and their thyroid function could not be assessed for all patients due to missing data. More studies are then needed to explore the effect of inappropriately treated hypothyroidism on delivery outcome.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…[21][22][23] Therefore, a prolonged uterine quiescent phase in late pregnancy could be hypothesized as a cause of fetal breech presentation, in addition to an inefficient uterine contraction pattern induced by a high thyroxine concentration state, resulting in an increase of overall CD rate. 4,12,21,[24][25][26] However, our study cannot support this hypothesis as the prescribed dosage, the women's adherence to levothyroxine therapy and their thyroid function could not be assessed for all patients due to missing data. More studies are then needed to explore the effect of inappropriately treated hypothyroidism on delivery outcome.…”
Section: Discussionmentioning
confidence: 79%
“…Based on the results our team previously demonstrated in fundamental research, we could presume a possible additional effect of levothyroxine due to overtreatment in hypothyroid pregnant women of our population. 11,12 Some clinical studies also documented an increased risk of CD and labor induction with hyperthyroidism, where women are exposed to high thyroxine serum concentrations due to a pathological overstimulation of thyroid hormone production. [21][22][23] Therefore, a prolonged uterine quiescent phase in late pregnancy could be hypothesized as a cause of fetal breech presentation, in addition to an inefficient uterine contraction pattern induced by a high thyroxine concentration state, resulting in an increase of overall CD rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that glibenclamide and metformin, drugs used in diabetes and PCOS, does not change the amplitude and frequency of spontaneous uterine contractions (23). It was found in another rat study that T4 treatment changes myometrial activity (24). After the observation of increased frequency of uterine contraction during ovarian stimulation cycles compared with the corresponding phase of natural menstruel cycles in a number of studies, a new pharmaterapeutic target arised and investigation of drugs reducing the contractility of uterus increased and conflicting results are found (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as term approaches, the quiescent uterus becomes activated byestrogens.This leads to increased expression of various contraction-associated proteins (CAPs) such as prostaglandin and oxytocin receptors [2]. Also, an increase in gap junction formation between adjacent myometrial cells allows electrical synchrony within the myometrium and ensures effective coordination of contractions [3]. During labor process, the frequency and intensity of myometrial smooth muscle contractions are essential contributing factors to normal delivery [4].…”
Section: Introductionmentioning
confidence: 99%